2020
DOI: 10.1002/aoc.5480
|View full text |Cite
|
Sign up to set email alerts
|

Application of titanium nanoparticles containing natural compounds in cutaneous wound healing

Abstract: The aim of the study was the rapid green synthesis of titanium nanoparticles using the aqueous extract of Falcaria vulgaris leaves (TiNPs@FV) and exploring their antioxidant, cytotoxicity, antifungal, antibacterial, and cutaneous wound healing activities under in vitro and in vivo condition. These nanoparticles were characterized by UV‐Vis, Fourier transform‐infrared(FT‐IR), X‐ray diffraction XRD), field emission‐scanning electron microscopy FE‐SEM), and transmission electron microscopy TEM) analyses. The synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Besides, the antioxidant nanoparticles can be used to eliminate toxic substances in the blood and treat acute myeloid leukemia. [34] Previous studies have suggested that peptides and proteins could be used to synthesize gold nanoparticles. [35] Chen et al proposed that gelatin could also be a suitable biomaterial by mixing gelatin with protein to make the polyionic complex (PIC) hydrogel network.…”
Section: Green Synthetic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the antioxidant nanoparticles can be used to eliminate toxic substances in the blood and treat acute myeloid leukemia. [34] Previous studies have suggested that peptides and proteins could be used to synthesize gold nanoparticles. [35] Chen et al proposed that gelatin could also be a suitable biomaterial by mixing gelatin with protein to make the polyionic complex (PIC) hydrogel network.…”
Section: Green Synthetic Methodsmentioning
confidence: 99%
“…This antioxidant compound has the ability to reduce gold ions into gold nanoparticles. Besides, the antioxidant nanoparticles can be used to eliminate toxic substances in the blood and treat acute myeloid leukemia [34] . Previous studies have suggested that peptides and proteins could be used to synthesize gold nanoparticles [35] .…”
Section: Synthesis Of Functionalized Gold Nanoparticlesmentioning
confidence: 99%
“…Although the chemical synthesis methods described above are effective, many of them suffer from some drawbacks such as high temperature, harsh reaction conditions, long reaction times, the use of toxic and aggressive chemicals as reducing and/or capping agents to control the size and composition of Au NCs, resulting in the environmental pollution caused by the use of organic solvents. [104][105][106][107] Besides, the toxic capping agents or chemicals used in the synthesis process tend to adsorb on the surface of Au NCs, which may cause severe threats to living cells while using Au NCs for drug delivery and diagnostic applications. [108][109][110][111][112] Consideration of the environmental problems, Firdhouse et al summarized the detailed advantages and disadvantages of conventional synthesis techniques for Au NPs synthesis.…”
Section: Synthesis Of Au Npsmentioning
confidence: 99%
“…Along with cutaneous wound healing, it was effective as both antibacterial and antifungal agent having bactericidal values in the range of 2-8 mg/mL and 2-16 mg/mL. It had excellent viability on human umbilical vein cells and hence proved to be extremely potential [82]. Recently, Shanmugasundaram et al…”
Section: Green Synthesized Nanoparticlesmentioning
confidence: 99%